Fashion Business Development Strategy In Terms Of Swot Analysis At Laksmi Muslim Fashion Boutique In Surabaya After The Co-19 Pandemic - Martha Suhardiyah; Sulistiami, Sulistiami; Aora Sapphire D; Gintan Regita Maharani (SEAN Institute, 2024)
The selection of the fashion business is based on the consideration that the fashion business is a category of small businesses that are most in demand by the community. therefore, efforts are needed to be able to win the competition to seize the market. Examining SWOT is a way of systematically collecting data on elements regarding strengths (Strengths), opportunities (Opportunities) weaknesses (Weaknesses) and Threats (Threats), This study uses a qualitative descriptive approach whose purpose is to describe the results of the fashion business development strategy at Laksmi Boutique Muslim Clothing in Surabaya.Sampling technique with total sampling, Data obtained using observation, interviews and document data collection. The conclusion of data analysis shows that to be able to win the competition the company must take more advantage by maximizing strengths (Strengths) and opportunities (Opportunities) through internal improvement of the company and can simultaneously reduce weaknesses (Weaknesses) and Threats (Threats) in business operations. Through this approach, business people have a basis for determining marketing and business development strategies with the right target.